Phase Angle is a Useful indicator for Muscle Function in Older Adults - Yamada, Minoru; Kimura, Y.; Ishiyama, D.; Nishio, N.; Otobe, Y.; Tanaka, T.; Ohji, S.; Koyama, S.; Sato, A.; Suzuki, M.; Ogawa, H.; Ichikawa, T.; et al. (The Journal of nutrition, health & aging, 2019)
Phase angle (PhA) can be determined through bioelectrical impedance analysis and is a unique variable for skeletal muscle. The objective of this study was to evaluate the relationship between PhA and muscle mass/quality in older adults. In addition, we attempted to determine the cutoff value of PhA for poor muscle function. Community-dwelling Japanese older men (n=285, 81.1±7.1 years) and women (n=724, 80.4±6.8 years) participated in this study and were classified into four groups based on the Asian Working Group for Sarcopenia (normal, presarcopenia, dynapenia, and sarcopenia). We measured PhA using bioelectrical impedance analysis, muscle quantity and quality indicators using ultrasonography, muscle strength, and physical performance and compared them in four groups. We also tried to determine the cutoff value of PhA for poor muscle function. We found a significant difference in PhA among the four groups in men (P<0.05), and the dynapenia (3.61±0.75°) and sarcopenia groups (3.40±0.74°) showed significantly lower values than the normal group (4.50±0.86°) (P<0.05), but not the presarcopenia group (4.12±0.85°). In women, a significant difference was also observed among the four groups (P<0.05), and the dynapenia (3.41±0.65°) and sarcopenia groups (3.31±0.66°) showed significantly lower measures than the normal group (4.14±0.71°) (P<0.05), but not the presarcopenia group (4.07±0.51°). The receiver-operating characteristic curve analysis indicated the best cutoff value of PhA (men: 4.05°, women: 3.55°) to discriminate sarcopenia and dynapenia from normal and presarcopenia. These findings suggest that PhA is a useful indicator for muscle function.